Response to Cardiac Resynchronization Therapy: The Muscular Metabolic Pathway - Jérémie Jaussaud; Pierre Blanc; Pierre Bordachar; Raymond Roudaut; Hervé Douard (Cardiology Research and Practice)
Background. Changes in peripheral muscle in heart failure lead to a shift from aerobic to early anaerobic metabolism during exercise leading to ergoreflex overactivation and exaggerated hyperventilation evaluated by the VE/VCO2 slope. Methods. 50 patients (38 males, 59±12 years) performed cardio-pulmonary exercise test with gaz exchange measurement and echocardiographic evaluation before and 6 months after CRT. Results. The peak respiratory exchange (VCO2/ VO2) ratio was significantly reduced from 1.16±0.14 to 1.11±0.07 (𝑃<.05) and the time to the anaerobic threshold was increased from 153±82 to 245±140 seconds (𝑃=.01). Peak VO2, VE/VCO2, peak circulatory power and NYHA were improved after CRT (13±4 to16±5 ml/kg/min (𝑃<.05), 45±16 to 39±13 (𝑃<.01), 1805±844 to 2225±1171 mmHg.ml/kg/min (𝑃<.01) and 3±0.35 to 1.88±0.4 (𝑃=.01)). In addition, left ventricular ejection fraction and end-systolic volumes were improved from 24±8 to 29±7% (𝑃<.01) and from 157±69 to 122±55 ml (𝑃<.01). Conclusion. We suggest that CRT leads to an increase in oxidative muscular metabolism and postponed anaerobic threshold reducing exaggerated hyperventilation during exercise.